Delirium in the Emergency Department: Moving From Tool‐Based Research to System‐Wide Change. Issue 5 (10th April 2020) - Kennedy, Maura; Hwang, Ula; Han, Jin H.
Abstract: This editorial comments on the article by.Malihot et al .